Sui giochi di potere dell’avanguardia: Velimir Chlebnikov, Daniil Charms e altri - Lada Panova (eSamizdat)
The article attempts to determine what makes the literary legacy of the first Russian avant-garde so special. Did Velimir Khlebnikov, Vladimir Maiakovskii, Daniil Kharms indeed pronounced a “New First Unexpected” word, as they claimed in their manifestos? On a closer look it turns out that their truly innovative feature consists not in their artistic output but rather in their self-promotion strategies resulting in power games in the field of Russian literature, in a sado-masochistic contract with the reader, and, last but not least, in the “How-to-kill-a-great predecessor” topos. Among other things, the article suggests a fresh approach to the avant-garde, which refuses to play its power games, does not accept its contract and concentrates instead on analyzing those.